KEMAMPUAN PENALARAN MATEMATIS PESERTA DIDIK MELALUI MODEL PEMBELAJARAN RECIPROCAL TEACHING DENGAN BERBANTUAN ALAT PERAGA â€œKARTU PINTARâ€ PADA MATERI PRISMA DAN LIMAS KELAS VIII SMP NEGERI 1 PANDAAN TAHUN AJARAN 2017/2018 - Putri Amalia Cahyani (Jurnal Pendidikan Matematika (JPM), 2019)
The purpose of this study was to determine whether there is an increase in mathematical reasoning abilities and to describe the mathematical reasoning abilities of students through the Reciprocal Teaching learning model assisted with "smart card" teaching aids on prism and pyramid material class VIII Public Middle School 1 Pandaan 2017/2018 Academic Year. The research method used in this study, which is a mixed method with an experimental mixed method design design, was to wrap a basic mixed method design into a further strategy, namely by adding processes into the experimental procedure. The results showed that based on the results of quantitative data analysis, it was concluded that there was an increase between mathematical reasoning abilities before and after using the Reciprocal Teaching learning model with the help of "smart card" teaching aids on class VIII prism and pyramid material in Pandaan 1 Public Middle School. From some of the data analysis shows that mathematical reasoning ability increases after the application of the Reciprocal Teaching learning model with the help of "smart card" teaching aids.